2012
DOI: 10.2319/010312-6.1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of personality on adult patients' adjustability to orthodontic appliances

Abstract: Anxious individuals tend to prefer lingual and clear aligner appliances. The selection of lingual and clear aligner appliances governs the patient's response and recovery process, leaving little room for the effect of psychological features. On the other hand, the buccal appliance allows for greater impact of personality traits on adjustability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…1, 2 The increasing demand for more aesthetic orthodontic appliances has elicited an aesthetic revolution marked by the emergence of invisible appliances, such as aesthetic brackets, lingual appliances, and clear aligners. 3, 4, 5 Among these appliances, clear aligners are often preferred over brackets by adults, owing to aesthetic and comfort considerations.…”
Section: Introductionmentioning
confidence: 99%
“…1, 2 The increasing demand for more aesthetic orthodontic appliances has elicited an aesthetic revolution marked by the emergence of invisible appliances, such as aesthetic brackets, lingual appliances, and clear aligners. 3, 4, 5 Among these appliances, clear aligners are often preferred over brackets by adults, owing to aesthetic and comfort considerations.…”
Section: Introductionmentioning
confidence: 99%
“…They found that younger patients who were extraverted, trustworthy, motivated, and agreeable were more likely to cooperate. Furthermore, using the Brief Symptom Inventory, CooperKazaz et al 15 observed that anxious individuals preferred lingual and clear aligner appliances over buccal appliances. To date, however, no studies have linked an individual's personality type with his probable willingness to undergo specific orthodontic treatment modalities.…”
Section: Introductionmentioning
confidence: 99%
“…The ndings of our research have veri ed their results in a different population with different psychological characteristics. In addition; Cooper-Kazaz et al [19] reported that personality traits and psychological features have signi cant impact on adjustability and recovery during xed buccal orthodontic treatment in adult patients; they used Brief Symptom Inventory to assess personality trait. Hansen et al [20] and Singh et al [21] observed that personality traits are useful in predicting a patient's potential willingness and cooperation during xed orthodontic treatments.…”
Section: Discussionmentioning
confidence: 99%